2018
DOI: 10.1093/hmg/ddy085
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of microRNA-15a and microRNA-15b in skeletal muscle from adult offspring of women with diabetes in pregnancy

Abstract: Offspring of women with diabetes in pregnancy exhibit skeletal muscle insulin resistance and are at increased risk of developing type 2 diabetes, potentially mediated by epigenetic mechanisms or changes in the expression of small non-coding microRNAs. Members of the miR-15 family can alter the expression or function of important proteins in the insulin signalling pathway, affecting insulin sensitivity and secretion. We hypothesized that exposure to maternal diabetes may cause altered expression of these microR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 44 publications
1
40
0
1
Order By: Relevance
“…In a community-based sample, miR-106b, miR-144, miR-15b, miR-451, and miR-93 were upregulated and miR-15a downregulated in skeletal muscle of individuals with type 2 diabetes compared to individuals with normal glucose tolerance 17 . In another study, higher levels of both skeletal muscle miR-15a and miR-15b were associated with higher fasting and 2-hour glucose in adults with and without diabetes 18 . Inconsistency of identified miRNAs in previous as well as the current study could be due to racial and ethnic differences in the study populations, heterogeneous mechanisms contributing to diabetes pathogenesis across the populations studied,or differences in methods (sample source, processing, and profiling).…”
Section: Discussionmentioning
confidence: 93%
“…In a community-based sample, miR-106b, miR-144, miR-15b, miR-451, and miR-93 were upregulated and miR-15a downregulated in skeletal muscle of individuals with type 2 diabetes compared to individuals with normal glucose tolerance 17 . In another study, higher levels of both skeletal muscle miR-15a and miR-15b were associated with higher fasting and 2-hour glucose in adults with and without diabetes 18 . Inconsistency of identified miRNAs in previous as well as the current study could be due to racial and ethnic differences in the study populations, heterogeneous mechanisms contributing to diabetes pathogenesis across the populations studied,or differences in methods (sample source, processing, and profiling).…”
Section: Discussionmentioning
confidence: 93%
“…Houshmand et al found that miR‐15a and miR‐15b were increased in expression in the adult offspring of women diagnosed with GDM during pregnancy. Furthermore, the offspring had significantly higher 2 hours plasma glucose values and borderline higher HbA1C levels …”
Section: Possible Associated Mechanism Between Mirnas and Dmmentioning
confidence: 97%
“…Furthermore, the offspring had significantly higher 2 hours plasma glucose values and borderline higher HbA1C levels. 60 Recently, the relationship between circulating levels of miRNAs and HbA1C levels has become another focus of current research.…”
Section: The Role Of Mirnas In Diabetic Complicationsmentioning
confidence: 99%
“…The function of miRNAs is modulated by binding to the 3 0 -UTR of target mRNAs, resulting in degeneration of mRNA and prohibition of translation (11). Previous studies have revealed that various miRNAs regulate the development of diabetes (12,13). Downregulation of miR-15a in the retina of patients with diabetes was found to counteract inflammation and generation of vessels (14).…”
Section: Introductionmentioning
confidence: 99%